Increasing Students' Interest in Learning Through the Application of Traditional Games in PJOK Learning - Wildan Fauzitama; Agus Cahyo Utomo; Anis Zawawi (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education has a very important role in human life, is fundamental, and cannot be separated from everyday life. The success of education is not only the responsibility of the government and related institutions, but also involves various other elements, including the role of teachers as educators and lecturers. This research aims to describe the application of traditional games in Physical Education, Sports and Health (PJOK) learning and analyze their influence on students' interest in learning. Using traditional game methods in learning PJOK can help students become more active in the learning process. Based on the research results, it can be concluded that the application of traditional games has a positive impact on increasing students' activeness and interest in learning in PJOK subjects at SDN Datengan 2 Kediri. This conclusion is supported by an increase in students' average scores and the percentage of learning completion from the pre-cycle stage, cycle I, to cycle II. This increase occurred because traditional games applied in PJOK learning were able to make students more active and motivated to learn.